2014
DOI: 10.1038/cddis.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analyses identify the involvement of microRNA-26a in epithelial–mesenchymal transition during idiopathic pulmonary fibrosis

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive, and highly lethal fibrotic lung disease with poor treatment and unknown etiology. Emerging evidence suggests that epithelial–mesenchymal transition (EMT) has an important role in repair and scar formation following epithelial injury during pulmonary fibrosis. Although some miRNAs have been shown to be dysregulated in the pathophysiological processes of IPF, limited studies have payed attention on the participation of miRNAs in EMT in lung fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 46 publications
5
64
0
1
Order By: Relevance
“…Variants in miRNAs have been reported to be correlated with a number of human diseases [22,23,24]. As shown by Jazdzewski et al, a C allele rs2910164 polymorphism significantly compromises the processing and maturing of miRNA and results in an approximately 2-fold decrease in production of mature miR-146a than a G allele in a thyroid cell line [25].…”
Section: Discussionmentioning
confidence: 97%
“…Variants in miRNAs have been reported to be correlated with a number of human diseases [22,23,24]. As shown by Jazdzewski et al, a C allele rs2910164 polymorphism significantly compromises the processing and maturing of miRNA and results in an approximately 2-fold decrease in production of mature miR-146a than a G allele in a thyroid cell line [25].…”
Section: Discussionmentioning
confidence: 97%
“…Tanjore et al [7] have demonstrated that EMT of alveolar epithelial cells contributes to fibroblasts in bleomycin (BLM)einduced lung fibrosis. It has been suggested that suppression of abnormal EMT process either with exogenous reagents such as methacycline and sorafenib [8,9] or endogenous regulators such as microRNA-26a and microRNA-21 [10,11] can ameliorate pulmonary fibrogenesis. These previous studies support a concept that EMT signaling is important to lung fibrosis, and inhibition of EMT may represent a useful approach to attenuate pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of miRNAs expressed in the lungs of IPF patients show significant deregulation. 17 It has been found that miRNA-326, 18 let-7d, miRNA-29, miRNA-18a, 17 miRNA-26a, [18][19][20] and miRNA-200 21 are downregulated and miRNA-21, 22 miRNA-199a, 23 and miRNA-145 24 are upregulated in lungs of IPF patients. Alterations in these miRNAs have also been demonstrated in lung fibroblasts or alveolar epithelial cells from IPF patients and pulmonary fibrosis animal models.…”
Section: Introductionmentioning
confidence: 99%